IMPLEMENTASI MODEL KOOPERATIF TPS UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PASSING SEPAKBOLA - ., I Kadek Budiantara; ., I Wayan Artanayasa, S.Pd, M.Pd.; ., I Made Satyawan, S.Pd. (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2014)
Penelitian ini bertujuan meningkatkan aktivitas dan hasil belajar passing sepakbola melalui implementasi model pembelajaran kooperatif tipe TPS pada siswa kelas X 7 SMA Negeri 1 Susut tahun pelajaran 2013/2014. Penelitian ini adalah Penelitian Tindakan Kelas yang dilaksanakan dalam dua siklus. Subjek penelitian siswa kelas X 7 SMA Negeri 1 Susut, berjumlah 38 orang. Data menggunakan analisis statistik deskriptif. Hasil analisis data pada observasi awal aktivitas belajar passing sepakbola secara klasikal sebesar 5,66 (cukup aktif) meningkat pada siklus I menjadi 7,21 (Aktif) dan siklus II menikat sebesar 9,1 (Aktif). Sedangkan ketuntasan hasil belajar passing sepakbola secara klasikal pada observasi awal 61,48 (Kurang Baik), siklus I meningkat sebesar 71,41 (Cukup Baik), pada siklus II meningkat sebesar 81,31 (Baik). Berdasarkan analisis data disimpulkan bahwa aktivitas dan hasil belajar passing sepakbola meningkat melalui implementasi model pembelajaran kooperatif tipe TPS pada siswa kelas X 7 SMA Negeri 1 Susut tahun pelajaran 2013/2014. Disarankan kepada guru penjasorkes dapat menggunakan model pembelajaran kooperatif tipe TPS karena dapat meningkatkan aktivitas dan hasil belajar passing sepakbola pada siswaKata Kunci : Kooperatif Tipe TPS, Aktivitas, Hasil Belajar, Passing Sepakbola This study was aimed to improve the students’ activity and achievement in learning football passing technique through the implementation of TPS cooperative learning model toward X7 grader students of SMA N 1 Susut academic year 2013/2014. This research was design im form of Classroom Action Research which was conducted in two cylces. The subject of this research was the X7 grader students of SMA N 1 Susut which consists of 38 students. The data gained were analyzed using descriptive statistic analysis. The result of data analysis shows that on the primary observation the activity of learning football passing technique classically was about 5.66 (active enough), and increased became 7.21 (active) in the first cycle and improved again in the second cycle became 9.1 (very active). Meanwhile, the learning achievement successfulness in learning football passing technique classically was 61.48 (bad) on the primary observation, and improved until 71.41 (good enough) in the first cycle and became 81.31 (good) in the second cycle. Therefore, based on the data analysis, it can be concluded that there are improvement in students’ activity and achievement in learning football passing technique through the implementation of TPS cooperative learning model toward X7 grader students of SMA N 1 Susut academic year 2013/2014. Finally, it can be used as a consideration for the sport science subject matter teachers to use TPS cooperative learning model as it can improve the students’ activity and achievement in learning football passing technique keyword : TPS cooperative learning model, Aktivity, Result study, passing Foot ball